PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT CITRA SELARAS NIAGA JAKARTA PUSAT - Mulia, Reza; Yanuarti, Maghfiroh (Jurnal Pijar, 2025)
The purpose of this research is to determine whether there is a partial influence of Leadership Style on Employee Performance at PT Citra Selaras Niaga Jakarta Pusat. This research method uses a quantitative associative method, data collection techniques using questionnaires. The population of this research is employees at PT Citra Selaras Niaga Jakarta Pusat with a population of 50 employees. Sampling used the saturated sample method, namely 50 employees. The research results show that Leadership Style has a significant effect on Employee Performance. The t-calculated value is greater than the t-table (3.626 > 2.008), with a significance value of 0.001, so it is smaller than 5%, namely 0.001 < 0.050, then Ha1 is accepted. Motivation has a significant effect on employee performance. The t-count value is greater than the t-table (3.043 > 2.008), with a significance value of 0.004, so it is smaller than 5%, namely 0.004 < 0.050, so Ha2 is accepted. Leadership Style and Motivation together influence employee performance. The F-calculated value is greater than the F-table (8.316 > 2.810), with a significance value of 0.001, so it is smaller than 5%, namely 0.001 < 0.050, then Ha3 is accepted